2016
DOI: 10.1080/14763141.2016.1171894
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of whole body vibration to the lower body in static and dynamic half-squat exercises

Abstract: Whole body vibration (WBV) is used as a training method but its physical risk is not yet clear. Hence, the aim of this study is to assess the exposure to WBV by a measure of acceleration at the lower limb under dynamic and static postural conditions. The hypothesis of this paper is that this assessment is influenced by the frequency, position, and movement of the body. Fifteen healthy males are exposed to vertical sinusoidal vibration at different frequencies (20-60 Hz), while adopting three different static p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…The transmissibility of the vibration during walking globally decreases with the distance from the point of interest to the ground in both the experiments. This result is in accordance with numerous studies indicating that the transmission of vibration is reduced above the knees while exposed to WBV (Matsumoto and Griffin, 1998;Munera et al, 2016) as well as to shock-induced vibrations when running (Chadefaux et al, 2019;Gruber et al, 2014). This phenomenon is supported by several hypotheses such as the dealignment of the segments (Vasconcellos et al, 2014) and the changes in the musclular mechanical properties with co-contraction (Heitmann et al, 2012).…”
Section: Vibration Transmissibilitysupporting
confidence: 92%
See 1 more Smart Citation
“…The transmissibility of the vibration during walking globally decreases with the distance from the point of interest to the ground in both the experiments. This result is in accordance with numerous studies indicating that the transmission of vibration is reduced above the knees while exposed to WBV (Matsumoto and Griffin, 1998;Munera et al, 2016) as well as to shock-induced vibrations when running (Chadefaux et al, 2019;Gruber et al, 2014). This phenomenon is supported by several hypotheses such as the dealignment of the segments (Vasconcellos et al, 2014) and the changes in the musclular mechanical properties with co-contraction (Heitmann et al, 2012).…”
Section: Vibration Transmissibilitysupporting
confidence: 92%
“…Since then, Morgado Ramirez et al (2013Ramirez et al ( , 2017 have studied the transmissibility of the spine during daily activities, and during walking to understand the difference in transmissibility between regions of the spine. Munera et al (2016) have also approached transmissibility of WBV at several bodies' location during half-squat exercises. However, a study to understand the apparent mass and transmissibility of the whole body at different locations during walking has yet to be published.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the identified frequencies, the frequency of 52.54 Hz is very similar to that found in previous studies [37,38]. Both resonance frequencies were determined by using a vibratory excitation at different frequencies between 10 and 90 Hz.…”
Section: Discussionsupporting
confidence: 75%
“…However, the dissipation of the vibrations' energy during WBV transmission is often reduced by other body tissues and structures. Therefore, the energy that reaches the target muscle(s) is often attenuated when propagated through the body 14 . Rubin et al 15 reported that when standing (20° knee flexion) on a vibration platform, transmission was dampened by the hip and spine (~30%).…”
Section: Discussionmentioning
confidence: 99%